2016
DOI: 10.1016/j.aorn.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Back to Basics: Preventing Perioperative Pressure Injuries

Abstract: Pressure injury prevention is essential to patient safety in the perioperative setting. Perioperative nurses should be knowledgeable about the risk factors for pressure injury and the safety precautions that can be taken to prevent this injury from occurring. Perioperative nurses should be able to identify patients who are at high risk for developing a pressure injury. Perioperative patients are at risk for developing pressure injuries because they can experience intense or prolonged pressure during lengthy su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
38

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 10 publications
0
63
0
38
Order By: Relevance
“…Many preventive intervention opportunities exist, such as the use of prophylactic multi-layer dressing, using alternative pressure mattress and vesico-elastic polymer pad (gel pad) on the operating table during surgery, patients' and caregivers' education on nutrition and skin care, frequent repositioning, and the use of positioning wedges. [38][39][40] Although many of these interventions had clinically demonstrated benefits for preventing PUs or accelerating the healing of PUs, some are costly or burdensome. Therefore, to avoid excessive cost and burden, we need to be able to identify cases of high risk and apply appropriate levels of prevention according to need.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many preventive intervention opportunities exist, such as the use of prophylactic multi-layer dressing, using alternative pressure mattress and vesico-elastic polymer pad (gel pad) on the operating table during surgery, patients' and caregivers' education on nutrition and skin care, frequent repositioning, and the use of positioning wedges. [38][39][40] Although many of these interventions had clinically demonstrated benefits for preventing PUs or accelerating the healing of PUs, some are costly or burdensome. Therefore, to avoid excessive cost and burden, we need to be able to identify cases of high risk and apply appropriate levels of prevention according to need.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge about preoperative risk factors is important so that nurses can implement preventive interventions before tissue injury begins. Many preventive intervention opportunities exist, such as the use of prophylactic multi‐layer dressing, using alternative pressure mattress and vesico‐elastic polymer pad (gel pad) on the operating table during surgery, patients' and caregivers' education on nutrition and skin care, frequent repositioning, and the use of positioning wedges …”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for perioperative pressure injuries are categorized as preoperative, intraoperative, or postoperative . Studies have reported that preoperative risk factors include advanced age; male sex; low body mass index (BMI); low hematocrit (ie, less than 38%), hemoglobin, and albumin levels; inadequate nutrition; diabetes mellitus and other chronic diseases (eg, respiratory, heart); and immobilization .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Risk factors for perioperative pressure injuries are categorized as preoperative, intraoperative, or postoperative. 8,9,17,18 Studies have reported that preoperative risk factors include advanced age; 6,19-23 male sex; 8 low body mass index (BMI); [21][22][23] low hematocrit (ie, less than 38%), 6,19 hemoglobin, 21,24 and albumin levels; 6,24 inadequate nutrition; 6,21 diabetes mellitus [19][20][21][22][23] and other chronic diseases (eg, respiratory, heart); 6,11,19,20,23 and immobilization. 9,11,21 Intraoperative risk factors include type of anesthesia, 6 procedure type 6,23 and duration, 6,19,21,22 intraoperative position of patient, 6,20 materials used for positioning, 8,11,20 the type of surface on the OR bed, 8 moist skin, 8,20 intraoperative vasopressor use, 22 intraoperative hypotension, intraoperative hypothermia (ie, temperature less than 36.5° C [97.7° F]) or hyperthermia (ie, temperature greater than 37.5° C [99.5° F]), and use of warming devices.…”
Section: Research Questionsmentioning
confidence: 99%
“…Successful pressure injury prevention strategies include risk assessment, standardization of equipment and devices, and implementation of AORN guidelines. 4,5…”
mentioning
confidence: 99%